2001
DOI: 10.1111/j.1574-6968.2001.tb10843.x
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate uniquely induces a 27-kDa protein in tubercle bacillus

Abstract: Salicylate was found to uniquely induce a 27-kDa protein in Mycobacterium tuberculosis complex organisms but not in Mycobacterium smegmatis or Escherichia coli. The structural analogue antitubercular para-amino-salicylate also induced the 27-kDa protein but to a somewhat lower level than salicylate. Other structural analogues such as benzoic acid and acetyl salicylic acid (aspirin) did not induce the 27-kDa protein. Western blot analysis indicated that the 27-kDa protein was localized mainly in the cytoplasm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…The following effects have been noted: reduction of adhesion to relevant biomatrices (29), reduction of capsule production (30), mitigation of biofilm formation (31), and diminution of vegetation growth, intravegetation bacterial proliferation, and hematogenous dissemination in experimental infective endocarditis (32). Salicylic acid also has been shown to upregulate the translation of specific gene loci, including multiple antibiotic-resistance loci (33); to induce cytoplasmic proteins (34); and to increase quinolone resistance (35). We recently studied the potential antimicrobial mechanisms of aspirin in the infective endocarditis model (8) and demonstrated that salicylic acid was the principal mediator of these antimicrobial effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The following effects have been noted: reduction of adhesion to relevant biomatrices (29), reduction of capsule production (30), mitigation of biofilm formation (31), and diminution of vegetation growth, intravegetation bacterial proliferation, and hematogenous dissemination in experimental infective endocarditis (32). Salicylic acid also has been shown to upregulate the translation of specific gene loci, including multiple antibiotic-resistance loci (33); to induce cytoplasmic proteins (34); and to increase quinolone resistance (35). We recently studied the potential antimicrobial mechanisms of aspirin in the infective endocarditis model (8) and demonstrated that salicylic acid was the principal mediator of these antimicrobial effects in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Rv0560c has been shown to be induced by salicylate (Sun et al, 2001), a compound that also increases oxygen consumption when added to M. tuberculosis cultures (Bernheim, 1940), and is clustered with other genes involved in ubiquinone biosynthesis (Sun et al, 2001). The function of Rv3866 is not known, but it is located just upstream of the virulence-associated RD1 element on the M. tuberculosis chromosome (Sassetti & Rubin, 2003).…”
Section: Cell Wallmentioning
confidence: 99%
“…Studies with cultured bacilli implicate PAS efflux via TAP as a potential resistance mechanism (121), yet a role for TAP in the limitation of PAS efficacy has yet to be established in infection models or in a clinical setting. Further, a PAS inactivation pathway involving the uncharacterized SAMdependent methyltransferase Rv0560c has been suggested (34,109,124,125) and may be the basis for methionine-linked antag- onism of PAS activity (81,82). Yet, whether this pathway limits the full potential action of PAS remains to be demonstrated.…”
Section: Closing Remarksmentioning
confidence: 99%